Intellectualization of Authorial Modality in Mоdern Ukrainian Prose Texts (Linguostylistic Studies, 2016)
The article attempts to describe the linguostylistic nature of the intellectual lexicon, actually the authorial modality aspect of it. The textual verbalization of the author’s language intellectualization concept is highlighted. The intellectual component of the authorial modality in the Ukrainian prose at the end of the XX – the beginning of the XXІ century has become firmly established as a combination of subjective, emotional and estimative modality. The communicative and pragmatic features and characteristics of contemporary prose caused the appearance of a significant number of lexemes, denoting general cultural concepts, abstract concepts, written text names, institutions, agencies, scientific terms, person names and others. The intellectual component of authorial modality has two levels: nominative and subjective-estimative. The nominative modality is superposed by subjective-estimative one, which expresses imaginative, philosophical, mental associations, personal intentions. Much attention is given to the author’s modality influence on linguocultural features of intellectual notions in the novels by Y. Andrukhovych, L. Deresh, S. Zhadan, I.Karpa, L.Kostenko, Y. Pashkovkiy. The article offers insights into idiostylistic characteristics of the authorial modality intellectualization in different narratives and reflections texts. Key words: intellectualization, modality, the authorial modality, intellectual lexicon, fiction, prose. References